2017
DOI: 10.1038/cddis.2016.492
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts enact field cancerization by promoting extratumoral oxidative stress

Abstract: Histological inspection of visually normal tissue adjacent to neoplastic lesions often reveals multiple foci of cellular abnormalities. This suggests the presence of a regional carcinogenic signal that spreads oncogenic transformation and field cancerization. We observed an abundance of mutagenic reactive oxygen species in the stroma of cryosectioned patient tumor biopsies, indicative of extratumoral oxidative stress. Diffusible hydrogen peroxide (H2O2) was elevated in the conditioned medium of cultured skin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 51 publications
2
101
0
Order By: Relevance
“…Recent studies have shown cancer-induced field defects influencing gene expression patterns in histologically normal tissues surrounding cancer (3,34,35). These observations raise a concern, as well as provide an opportunity for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown cancer-induced field defects influencing gene expression patterns in histologically normal tissues surrounding cancer (3,34,35). These observations raise a concern, as well as provide an opportunity for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs are one of the major components of tumor stroma which not only directly influence tumor cells but also influences other types of cells in form of stimulation (e.g., recruitment of endothelial cells) or inhibition (e.g., exclusion of T-cells) leading to the establishment of a tumor-permissive microenvironment [107]. An activated CAF phenotype is associated with elevated microenvironmental oxidative stress that might, in turn, stimulate genetic changes in the epithelial cells and normal stromal fibroblasts and their cancer transformation [116]. Based on the heterogeneity of expressed markers, CAFs have been suggested to derive from different cellular origins, for example, activation of resident fibroblasts, recruitment of bone marrow derived progenitor cells to the tumor site, and trans-differentiation through the endothelial-mesenchymal or epithelial-mesenchymal transition as reviewed recently by Levesque and Nelson [107].…”
Section: Pcsc Nichementioning
confidence: 99%
“…Moreover, ROS can activate the MAPK pathways which the activation of ERK, JNK, and p38 MAPK signaling proteins were involved in apoptosis via ROS generation. Studies have demonstrated the MAPK pathways, plays a pivotal role in cell survival and the enhanced protection of cancer cells from apoptosis during tumorigenesis [150]. Modulation of MAPK by Antioxidant is also involved in the therapy such as heart failure model [151].…”
Section: Ros and Diseasesmentioning
confidence: 99%